Price and utilisation differences for statins between four countries. (2nd January 2018) - Thai, Loc Phuoc; Vitry, Agnes Isabelle; Moss, John Robert
ABSTRACT: Introduction : Australia, England, France and New Zealand use different policies to regulate their medicines market, which can impact on utilisation and price. Objectives : To compare the prices and utilisation of statins in Australia, England, France and New Zealand from 2011 to 2013. Methods : Utilisation of statins in the four countries was compared using Defined Daily Doses (DDD) per 1000 inhabitants per year. Pairwise Laspeyres and Paasche index comparisons were conducted comparing the price and utilisation of statins. Results : The results showed that the price of statins in New Zealand was the cheapest. The price of statins in Australia was most expensive in 2011 and 2012 but France was more expensive in 2013. There were large differences between the Laspeyres index and Paasche index when comparing the price and utilisation of England with Australia and France. Discussion : The policies that regulate the New Zealand and England medicines markets were more effective in reducing the price of expensive statins. The relative utilisation of cheaper statins was greatest in England and had a large effect on the differences between the two index results. The pricing policies in Australia have been only partly effective in reducing the price of statins compared to other countries.